A study on customer's satisfaction towards the value added services by Telekom Malaysia (TM) / Norafizah Basirin - Basirin, Norafizah (2011)
The purpose of this study is to identify the level of customer's satisfaction towards the Value-Added Services provided by Telekom Malaysia(TM). This study aims on determine on how does the product diversity, tangibles, responsiveness, interaction, and stability will influence the customer's satisfaction as according to the research model in this study. In this study, data which is collected from 120 respondents around the area of Kota Kinabalu will be analyzed using frequency analysis, crosstabulation analysis, and linear regression analysis. The results of this study suggest that although the product diversity, tangibles, responsiveness, interaction, and stability of the Value-Added Services is available, due to the reason that the respondents involvement in the Value-Added Services is low, therefore it suggest that their satisfaction is low as the result of not fully aware to the Value-Added Services provided. This study also suggest that the factors that mostly influencing the respondents awareness is through TM Point and Family & Friends, while the factors that mostly influencing the respondents satisfactions towards the Value-Added Services is responsiveness, tangibility, and stability.